Evaluation Of Haematinic Activity of Bauhinia Purpurea Leaves Under In-Vivo Models - Sudheer, Akkiraju; N. Keerthana, N. Keerthana; B. Dhanush, B. Dhanush; Geethanjali, Bukke; Sushma, Papireddypalli; Ganga, T R Harini; Vomo, Joshua Anthony; Reddy, Kanala Somasekhar (Journal of Neonatal Surgery, 2025)
The haematinic activity of an orally administered ethanolic extract of Bauhinia purpurea leaves was studied on haemolytic anaemic rats. Anaemia was induced by oral administration of phenyl hydrazine for a period of 14 days. red blood cell count, haemoglobin concentration, and packed cell volume were analysed as indices of anaemia. The mean cell haemoglobin, mean cell volume and mean cell haemoglobin concentration were calculated accordingly. Phenyl hydrazine induced a significant decrease (p<0.05) in the blood indicating anaemia and also resulted to significant increase(p<0.05) in the mean cell haemoglobin, mean cell volume values, which are indicator of macrocytosis. leaf extract of Bauhinia purpurea induced a significant (p<0.05) increase in the red blood cell count, haemoglobin concentration, and packed cell volume which has been originally decreased by phenyl hydrazine administration 14 days of treatment. The presence of macrocytosis turn towards normal as the animal recovered from anaemic condition. The results obtained suggested that bauhinia purpurea leaves have hematinic activity